Performance of the Multidimensional Geriatric Assessment and Multidimensional Prognostic Index in predicting negative outcomes in older adults with cancer. (10th October 2016) - Giantin, V.; Falci, C.; De Luca, E.; Valentini, E.; Iasevoli, M.; Siviero, P.; Maggi, S.; Martella, B.; Crepaldi, G.; Monfardini, S.; Manzato, E.
Abstract : The Multidimensional Geriatric Assessment (MGA) is currently used for assessing geriatric oncological patients, but a new prognostic index ‐ the Multidimensional Prognostic Index (MPI) ‐ has a demonstrated prognostic value in cancer patients too. The present work was designed to compare the MPI and MGA as predictors of 12‐month mortality. 160 patients ≥70 years old with locally‐advanced or metastatic solid cancers consecutively joining our Geriatric Oncology Program were administered a Comprehensive Geriatric Assessment to calculate their MGA and MPI scores. Settings: Geriatric Clinic, Geriatric Surgery Clinic, Medical Oncology Unit, Padova Hospital, Italy. Using Cohen's Kappa coefficient, there was a poor concordance between the MPI and MGA. Severe MPI being associated with a higher mortality risk than Frail in the MGA. The ROC curves indicated that the MPI had a greater discriminatory power for 12‐month mortality than the MGA. In our population of elderly cancer patients, the MPI performed better than the MGA in predicting mortality. Further evidence from larger prospective trials is needed to establish whether other geriatric scales, such as the GDS and CIRS‐SI, could enhance the value of prognostic indexes applied to elderly cancer patients.